DESCONTMARKS: scale development and validation - Ismail, An Nur Nabila; Abdul Aziz, Yuhanis; Kamal Basha, Norazlyn; Bali Mahomed, Anuar Shah (Canadian Center of Science and Education, 2021)
In order to attract more tourists to visit a particular place, destination content marketing plays an important role. Tourism research has recently shown an interest in destination content marketing; especially when tourism destination is advertised. Currently, there is no scale available to measure content marketing for promoting tourism destination. The present study has two primary objectives. First, to investigate the dimension of destination content marketing in destination related context. Second, to develop and validate a multiple-item scale for measuring content marketing towards tourism destination. This study uses a rigorous scale development technique which involves three stages of scale development using 3 separate studies. The study confirms that destination content marketing scale (DESCONTMARKS) comprises of three dimensions, measured with 10 items. The implications of the destination content marketing scale for practitioners, as well as suggestions for future research are provided.